The Influences of Different Winemaking Techniques on the Mouthfeel of Shiraz Grapes - Nel, A.P.; Louw, L.; Lambrechts, M.G.; van Rensburg, P. (South African Journal of Enology and Viticulture, 2016)
The objective of this study was to determine the effect of ripeness and of different tannin extraction methods on the sensory properties of wine, with a specific focus on mouthfeel properties. Quantitative descriptive analysis (QDA) was performed to evaluate the sensory properties of 20 young Shiraz wines in two phases. In Phase 1, wines from a cool area were evaluated and, in Phase 2, wines from a warm area were evaluated. Clear differences were found between the wines from the two regions. Wines from the cooler region were generally associated with higher levels of total non-flavonoids and total anthocyanins, and more intense numbing and puckering sensations. In contrast, the wines from the warmer region as a group were associated with a more drying and grippy mouthfeel, as well as less total anthocyanins and total non-flavonoids. In the set of wines from the cooler region, the effect of ripeness was more pronounced than in the set of wines from the warmer region. In both cases, riper grapes resulted in a coarser surface smoothness, a more numbing sensation, a bitter aftertaste and less adhesive mouthfeel. The wines from the cooler region that were harvested at a riper stage were associated with many of the anthocyanins/ anthocyanin derivatives and were negatively associated with hydroxycinnamate, procyanidin B1 and delphinidin-3-glucoside-p-coumaric acid. In the warmer area, the riper grapes were again associated with anthocyanins/anthocyanin derivatives, but this time were strongly associated with procyanidin B2, caffeic acid, p-coumaric acid, catechin, coutaric acid and total non-flavonoids. The effect of tannin extraction method on the sensory properties of the wines from the warmer region was more pronounced than in the wines from the cooler region. Unfortunately, the differentiation between treatments was not consistent from one ripeness level to the next. However, it appeared that the cold soak treatment differed the least from the control, regardless of region or ripeness, whereas the post-maceration treatment differed the most based on mouthfeel and phenolic composition. Although some mouthfeel attributes and phenolic compounds were consistently associated with region and ripeness, it is not clear if mouthfeel can be manipulated consistently by tannin extraction methods.